Anatomical in vivo study of variations in zygomatic bone: pneumatization and foramina - Carvalho, César Felipe de Gouvêa; Tolentino, Elen de Souza; Herreira-Ferreira, Matheus; Takeshita, Wilton Mitsunari; Iwaki, Lilian Cristina Vessoni; Chicarelli, Mariliani (Acta Scientiarum. Health Sciences, 2022)
To determine the prevalence and characteristics of the zygomatic bone pneumatization (ZBP) and the presence and diameter of zygomaticofacial (ZFF), zygomaticoorbital (ZOF) and zygomaticotemporal (ZTF) foramina, correlating the findings with sex, age and facial skeletal pattern using cone beam CT (CBCT). 563 CBCT scans (1,126 ZB) were assessed and the type (uni/multilocular) and laterality of ZBP were determined, in addition to the presence and diameter of ZFF, ZOF and ZTF. Data was correlated with sex, age and facial pattern. 64 patients (11.37%) presented ZBP, with no differences among sex, age, facial patterns and types (p>0.05). Most pneumatizations were bilateral (68%; p<0.01). ZFF, ZOF and ZTF were detected in 926 (82.2%), 988 (87.7%) and 818 (72.6%) ZB, respectively. Differences were found for ZFF between age groups (p <0.005; >21-60 years). No differences were found for diameters (p >0.05). There is no relationship between sex, age and facial skeletal pattern with the presence of ZBP. The presence of ZFF was related to the age group. The knowledge about ZB anatomy and its variations is helpful for image interpretation as part of clinical and surgical treatment planning for this region.